Anticoagulant Usage Following Anterior Cruciate Ligament Reconstruction is Associated with Increased Rate of Manipulation Under Anesthesia. Issue 7 (31st July 2020) - Malahias, Michael-Alexander; Wessel, Lauren; Richardson, Shawn; Doerre, Teresa; Stake, Seth; Sculco, Peter; Rodeo, Scott; Kaar, Scott; Gu, Alex
Objectives: Although uncommon, arthrofibrosis following anterior cruciate ligament reconstruction (ACLR) is considered to be a significant and disabling complication for a young, athletic population. In this study, we aimed to determine: (1) the prevalence of manipulation under anesthesia (MUA) for treatment of arthrofibrosis following ACLR (2) whether anticoagulant use following ACLR is associated with an increased risk of MUA. We anticipate that postoperative use of anticoagulants will be associated with an increased risk of subsequent MUA. Methods: A retrospective cohort study was conducted using data collected from the Humana insurance database using the PearlDiver Patient Records Database from 2007-2017. Subjects were identified using Current Procedural Terminology (CPT) and International Classification of Diseases (ICD) codes. Patients were initially identified by ACL sprain or tear diagnosis utilizing ICD codes. Patients who underwent a concomitant MCL, PCL or LCL repair or reconstruction were excluded from this analysis. Patients who underwent MUA within one year of ACLR were then identified. Patient demographic characteristics including age, sex, and Charlson Comorbidity Index (CCI) were recorded. In addition, previously identified risk factors for knee stiffness were collected, including history of diabetes mellitus and obesity. Lastly, the time between ACL tear and surgery and ACL reconstruction to MUA were collected and categorized into 2 groups: (1) <4 weeks and (2) >4 weeks. Anticoagulants included in this analysis were warfarin, aspirin, low-molecular-weight heparin, direct factor Xa inhibitors and fondaparinux. Patient demographics, comorbidities, timing to surgery, concomitant meniscal repair, and postoperative complications were analyzed with a logistic multivariate analysis to determine adjusted associations of risk factors of arthrofibrosis. A p-value of < 0.05 was used as the cutoff for statistical significance. Results: There were 7, 798 patients who met the inclusion criteria for this analysis. 115 (1.5%) patients received a subsequent MUA within one-year, while 7, 683 (98.5%) patients did not. Among patients who underwent ACLR, 234 (3.0%) patients were on anticoagulants postoperatively. Patients who were on anticoagulants following ACLR were more likely to require an MUA (OR: 4.626; 95% CI: 2.462-8.093; p<0.001; Table 1). Other risk factors for MUA are listed in Table 1. Conclusion: The key finding of this study was that the use of anticoagulants is associated with increased rates of MUA following ACLR. One potential mechanism for the effect of anticoagulants may be the increased risk of postoperative hematoma. Recurrent hematoma has been suggested as a risk factor for arthrofibrosis requiring MUA following ACLR due to increased vascular micro-permeability that anticoagulants can produce. The presence of blood products in the joint may stimulate the accumulation of inflammatory mediators and subsequent fibrosis, as it is well-established that unresolved inflammation can initiate and propagate scar tissue formation. In conclusion, arthrofibrosis after ACLR is associated with postoperative use of thromboprophylaxis. Healthcare providers should be cognizant of this risk when considering anticoagulant usage in this patient population.